Zinc as a micronutrient and its preventive role of oxidative damage in cells. Issue 10 (19th August 2015) - Kloubert, Veronika; Rink, Lothar
Abstract : Zinc deficiency leads to increased ROS production, thereby causing lipid peroxidation. Subsequently, signalling via the NF-κB pathway is increased, resulting in the expression of pro-inflammatory cytokines which in turn cause chronic inflammatory diseases. Abstract : Zinc is an essential trace element with special importance in the immune system. Deficiencies of zinc are seen in the course of ageing and in various diseases, such as diabetes mellitus or rheumathoid arthritis. The trace element is essential for a variety of basic cellular functions and especially important for various enzymes participating in the production and neutralization of reactive oxygen species (ROS) which are normally produced by the cell. Under normal conditions ROS are neutralized and are not able to harm the cell, but in case of ROS elevation, oxidative damage within the cell is the result. Interestingly, zinc deficiency is directly associated with oxidative stress. Thus, control and regulation of the intracellular zinc content is essential with participation of various transporter and zinc-binding proteins, such as metallothionein. Oxidative stress is mainly caused by elevated ROS production and a decrease of antioxidant mechanisms. Zinc partly functions as an antioxidant although it is redox inert. Zinc supplementation is associated with decreased ROS formation exhibiting beneficial effects especially in ageing and diabetes mellitus. This review summarizes current findings concerning zinc as a micronutrient and its actions as a pro-antioxidant, and the association between zinc and oxidative stress under various conditions is highlighted.